Temperature Dependence of Chlorophyll Triplet Quenching in Two Photosynthetic Light-Harvesting Complexes from Higher Plants and Dinoflagellates - Vinklárek, Ivo S; Bornemann, Till L V; Lokstein, Heiko; Hofmann, Eckhard; Alster, Jan; Pšenčík, Jakub (The journal of physical chemistry. B, 2018)
Chlorophyll (Chl) triplet states generated in photosynthetic light-harvesting complexes (LHCs) can be quenched by carotenoids to prevent the formation of reactive singlet oxygen. Although this quenching occurs with an efficiency close to 100% at physiological temperatures, the Chl triplets are often observed at low temperatures. This might be due to the intrinsic temperature dependence of the Dexter mechanism of excitation energy transfer, which governs triplet quenching, or by temperature-induced conformational changes. Here, we report about the temperature dependence of Chl triplet quenching in two LHCs. We show that both the effects contribute significantly. In LHC II of higher plants, the core Chls are quenched with a high efficiency independent of temperature. A different subpopulation of Chls, which increases with lowering temperature, is not quenched at all. This is probably caused by the conformational changes which detach these Chls from the energy-transfer chain. In a membrane-intrinsic LHC of dinoflagellates, similarly two subpopulations of Chls were observed. In addition, another part of Chl triplets is quenched by carotenoids with a rate which decreases with temperature. This allowed us to study the temperature dependence of Dexter energy transfer. Finally, a part of Chls was quenched by triplet-triplet annihilation, a phenomenon which was not observed for LHCs before.
Keywords: Cold Temperature; světlo; světlosběrné proteinové komplexy; Spinacia oleracea; Chlorophyll A; chlorofyl; Energy Transfer; nízká teplota; Dinoflagellida; Light-Harvesting Protein Complexes; Dinoflagellata; Carotenoids; karotenoidy; Light; chlorofyl a; Chlorophyll; přenos energie